2016
DOI: 10.3354/meps11899
|View full text |Cite
|
Sign up to set email alerts
|

Vibrissal growth parameters of southern elephant seals Mirounga leonina: obtaining fine-scale, time‑based stable isotope data

Abstract: Stable isotopes provide a powerful, indirect approach to assess the trophic ecology of individuals on a spatial and temporally integrated basis (especially when combined with telemetry). However, using stable isotopes requires accurate, species-specific quantification of the period of biomolecule deposition in the sampled tissue. Sequentially sampled vibrissae (whiskers) provide a chronology of biogeochemical data, although knowledge of the vibrissal growth is required for temporal interpretations. We sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…These estimates assume a constant growth rate, which likely does not occur in this species based on Beltran et al (2015), but allowed for direct comparison with available estimates in the phocid literature. Beltran et al (2015) and Lübcker et al (2016) reported that elephant seal vibrissa growth follows a von Bertalanffy pattern consistent with other phocids (McHuron et al 2016), in the form:…”
Section: Vibrissa Linear Growth Ratessupporting
confidence: 61%
See 1 more Smart Citation
“…These estimates assume a constant growth rate, which likely does not occur in this species based on Beltran et al (2015), but allowed for direct comparison with available estimates in the phocid literature. Beltran et al (2015) and Lübcker et al (2016) reported that elephant seal vibrissa growth follows a von Bertalanffy pattern consistent with other phocids (McHuron et al 2016), in the form:…”
Section: Vibrissa Linear Growth Ratessupporting
confidence: 61%
“…Observations of freeranging and captive seals, however, suggest that seasonal molting patterns may be partially or completely absent in leopard seals Hydrurga leptonyx (Hall-Aspland et al 2005), harbor seals Phoca vitulina (Greaves et al 2004), southern elephant seals Mirounga leonina (Newland et al 2011), and northern elephant seals Mirounga angustirostris (Beltran et al 2015). For example, 71% of southern elephant seals shed their vibrissae during the annual pelage molt (Lübcker et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, phocid whisker growth rates are nonlinear (Hirons et al 2001; Zhao and Schell 2004;Newland et al 2011) and vary by location across the muzzle (Greaves et al 2004;Beltran et al 2015;McHuron et al 2016). These sources of variability make it difficult to use stable isotope analysis of whiskers as a tool for quantifying foraging ecology because estimating stable isotope deposition date requires specificity in individual whisker initiation date, growth rate, final whisker length (asymptotic length), and number of days grown (Sadou et al 2014;Beltran et al 2015;Lübcker et al 2016;McHuron et al 2016). Previous studies have used repeat photogrammetry of growing phocid whiskers across the muzzle to describe asymptotic growth (von Bertalanffy 1968), and the timing of whisker shed once it reaches asymptotic length (Greaves et al 2004;Beltran et al 2015;Lübcker et al 2016;McHuron et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These sources of variability make it difficult to use stable isotope analysis of whiskers as a tool for quantifying foraging ecology because estimating stable isotope deposition date requires specificity in individual whisker initiation date, growth rate, final whisker length (asymptotic length), and number of days grown (Sadou et al 2014;Beltran et al 2015;Lübcker et al 2016;McHuron et al 2016). Previous studies have used repeat photogrammetry of growing phocid whiskers across the muzzle to describe asymptotic growth (von Bertalanffy 1968), and the timing of whisker shed once it reaches asymptotic length (Greaves et al 2004;Beltran et al 2015;Lübcker et al 2016;McHuron et al 2016). Recently, these phocid whisker growth models have been used to quantify foraging behavior by using the von Bertalanffy (1968) organic growth equation to estimate the timing of stable isotope deposition (Lübcker et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation